Artificial intelligence for dummies - Mueller, John 1958-; Massaron, Luca (Gildan Audio, 2019)
Step into the future with AI The term "Artificial Intelligence" has been around since the 1950s, but a lot has changed since then. Today, AI is referenced in the news, books, movies, and TV shows, and the exact definition is often misinterpreted. Artificial Intelligence for Dummies provides a clear introduction to AI and how it's being used today. In this book, you'll get a clear overview of the technology, the common misconceptions surrounding it, and a fascinating look at its applications in everything from self-driving cars and drones to its contributions in the medical field. The world of AI is fascinating-and this hands-on guide makes it more accessible than ever!
Downloadable audio file
Keywords: Computers; Ordinateurs; computers; COMPUTERS / Intelligence (AI) & Semantics; Downloadable audio books; Audiobooks; Livres audio